ENGLISH GRAMMAR TEACHING ENHANCEMENT: FROM RULES TO REASON-BASED APPROACH - Kosheleva, I. N. (Вестник Кемеровского государственного университета, 2018)
When describing grammar phenomena, many course-books comprise rules of thumb and turn students’ attention to the construction methods of grammar forms. However, in practice these rules can be abstract, not giving precise or full explanation to the language units. In some cases explanations don’t correspond to the examples from the authentic sources. The subject of this research is the problem of the effective teaching English grammar to the students of non-linguistic universities. The purpose of the article is to describe methods of teaching English grammar from the standpoint of meaning of the grammar phenomenon and taking into consideration its contextual use. The current research is based on the ideas and concepts of the communicative approach to language teaching, conscious-raising approach and the method of the contextual use of language material. The paper features a number of advantages of the reason-based approach over the presentation of the rule. The approach enables students to notice and compare different contextual use cases of the language units. Therefore, it lays foundation for internalization of the new linguistic material and its further use in real communication. The results of the research can be of interest to both foreign language teachers and to the researchers dealing with English grammar learning. The conclusion is that the approach in question gives a more precise description of the meaning or use of grammatical constructions. It allows one to understand native speakers’ logic and intentions, which significantly facilitates intercultural communication.